PENTINGNYA ASPEK GOVERMENT POWER DALAM PENGEMBANGAN INDUSTRI PARIWISATA DAERAH - Windhyastiti, Irany; Widiawati, Diah (Jurnal Manajemen dan Kewirausahaan, 2016)
The tourism industry has the characteristic interdependence : (1) Hospitality Industry (Food and Baverage, and accommodation); (2) Travel (Retail and Wholeseller; The operator); (3) Visitor Services (Attraction; Event; and Tourism Agencies). Therefore, to build a strong tourism industry needed a strong organisational relationships. Power and dependence is an important basic building cooperation between organizations. One of the cities in Indonesia that are prominent in tourism is Kota Batu. Kota Batu is the icon of tourism in East Java. Even in the year 2006-2007, the industry of tourism in Kota Batu had dropped shraply because of overflow of Lapindo mud. In 2012, the total tourists visiting the Kota Batu reached 1,603,441 visitors. In 2013 increased 1,881,446 and 2,089,022 tourists in 2014. That number rises quickly compared in 2007, when the condition of the Kota Batu dropped as the number of tourist visits less than 1 million people. Now, in 2016, The government of Kota Batu target revenue of Rp 1 trillion, where 80% is derived from the tourism sector. Therefore, in the study will be analized how the government power in developing the tourism industry in Kota Batu. The technical analysis of this research uses a combination of analysis statistics and policy analysis. The analysis unit of this study is the tourism industry in Kota Batu. This research population are the stakeholders in the tourism industry : tourism entrepreneur and community. Based on the statistics analysis, the aspect of power has significant influence towards the development of the tourism industry. This shows the importance of the government role in developing the tourism industry.